POTENSI INHIBITOR SENYAWA PADA SUKUN (Artocarpus altilis) TERHADAP PROTEIN POLY (ADP-RIBOSE) POLYMERASE 2 (PARP2) PADA KANKER OVARIUM DENGAN MODEL MOLECULAR DOCKING: Inhibitor Potency of Compounds in Breadfruit (Artocarpus altilis) Against Protein Poly (ADP-Ribose) Polymerase 2 (PARP2) in Ovarian Cancer with The Molecular Docking Model - I Putu Bayu Agus Saputra; Ni Made Wiasty Sukanty; I Putu Deddy Arjita; I Gede Angga Adnyana (Universitas Muhammadiyah Surakarta, 2023)
ABSTRACT Ovarian cancer is the third leading cause of cancer death in Indonesia. The mechanism of cancer needs to be understood to create drugs that play a role in inhibiting the development of cancer cells. PARP is a prime protein in cancer cell development. PARP is a target of chemotherapy, namely through its inhibition by 3-aminobenzamide compounds. Treatment using natural ingredients is safer than using synthetic drugs. Breadfruit (Artocarpus altilis) is a plant that grows in Indonesia. It is efficacious because it contains many compounds used in the manufacture of various types of drugs. The PARP receptor (3KCZ) was examined for the value of binding affinity with the flavonoid derivative ligands contained in breadfruit (Artocarpus altilis) using the help of the software Pyrx version 0.8. The test results showed tamoxifen (-8 kcal/mol), quercetin (-8 kcal/mol), cyclocommunal (-9.6 kcal/mol), morusin (-6.7 kcal/mol), and cyclomulberrin (-9 kcal /mol) have a lower binding affinity value compared to 3-aminobenzamide (-6.6 kcal/mol) which is the native ligand of PARP. These results prove that the flavonoid-derived compounds in breadfruit can potentially act as PARP inhibitors in ovarian cancer cells. ABSTRAK Kanker ovarium merupakan kanker penyebab kematian ketiga terbesar di Indonesia. Mekanisme kanker sangat perlu dipahami untuk menciptakan obat yang berperan menghambat perkembangan sel kanker. PARP merupakan protein yang berperan penting pada perkembangan sel kanker. PARP telah terbukti dapat menjadi target kemoterapi, yaitu melalui penghambatannya oleh senyawa 3-aminobenzamide. Pengobatan menggunakan bahan alami lebih aman dibandingkan penggunaan obat sintetis. Sukun (Artocarpus altilis) merupakan tumbuhan yang tumbuh di Indonesia yang berkhasiat karena mengandung senyawa yang dapat dimanfaatkan dalam pembuatan berbagai jenis obat. Reseptor PARP (3KCZ) dilihat nilai binding affinity dengan ligan turunan flavonoid yang terkandung pada sukun (Artocarpus altilis) menggunakan bantuan softwere pyrx versi o,8. Hasil uji menunjukkan senyawa tamoxifen (-8 kcal/mol), quercetin (-8 kcal/mol), cyclocommunal (-9,6 kcal/mol), morusin (-6,7 kcal/mol), dan cyclomulberrin (-9 kcal/mol) memiliki nilai binding affinity yang lebih kecil dibandingkan dengan 3-aminobenzamide (-6,6 kcal/mol) yang merupakan native ligan dari PARP. Hasil ini membuktikan bahwa senyawa-senyawa turunan flavonoid pada sukun dapat berpotensi sebagai inhibitor PARP pada sel kanker ovarium.